Pelestarian Terbitan Berkala Koleksi Perpustakaan Nasional Republik Indonesia dengan Metode Penjilidan “Malaysia” - Damaji Ratmono (Perpustakaan Nasional, 2021)
Preservation of library materials or library collections is an effort made so that library materials can be used by future generations. This paper describes the